2016
DOI: 10.35188/unu-wider/2016/163-5
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal inequalities and affirmative action: An analysis of attitudes towards redistribution across groups in Africa

Abstract: This study has been prepared within the UNU-WIDER project on 'Discrimination and affirmative actions-what have we learnt so far?', which is part of a larger research project on 'Disadvantaged groups and social mobility'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We thus depart from traditional political economy applications that assume that ethnic groups share a "taste for discrimination" (Becker, 1971) or have a commonality of tastes for which ethnic group members may only be willing to bear the cost of providing public goods if their co-ethnics are the primary recipients (see, for instance, Sambanis & Shayo, 2013;Schmidt-Catran, 2016; while Miguel & Gugerty, 2005, also examine this mechanism, their evidence does not support it). Since past studies could not establish ethnic discrimination to occur in experimental games unless threatened with social sanctions (for the Ugandan context see Habyarimana et al, 2007) and support for economic redistribution to poorer ethnic groups seems high across a number of sub-Saharan contexts (Langer & Mikami, 2013;Langer et al, 2016), we expect that equity considerations are common across groups: H2. Kenyan citizens who attribute the relative disadvantage of the poorest ethnic groups to past political exclusion and historical discrimination are likely to be more supportive of HR.…”
Section: Theorizing Support For Redistributionmentioning
confidence: 99%
See 2 more Smart Citations
“…We thus depart from traditional political economy applications that assume that ethnic groups share a "taste for discrimination" (Becker, 1971) or have a commonality of tastes for which ethnic group members may only be willing to bear the cost of providing public goods if their co-ethnics are the primary recipients (see, for instance, Sambanis & Shayo, 2013;Schmidt-Catran, 2016; while Miguel & Gugerty, 2005, also examine this mechanism, their evidence does not support it). Since past studies could not establish ethnic discrimination to occur in experimental games unless threatened with social sanctions (for the Ugandan context see Habyarimana et al, 2007) and support for economic redistribution to poorer ethnic groups seems high across a number of sub-Saharan contexts (Langer & Mikami, 2013;Langer et al, 2016), we expect that equity considerations are common across groups: H2. Kenyan citizens who attribute the relative disadvantage of the poorest ethnic groups to past political exclusion and historical discrimination are likely to be more supportive of HR.…”
Section: Theorizing Support For Redistributionmentioning
confidence: 99%
“…Perceptions of political exclusion and disfavoring might be more significant in explaining support for HR, however, than actual histories of in-and exclusion and ethnic favoritism, as was the case in Nigeria and Uganda (Langer et al, 2016). Notably, while past research has shown that there is consistency between objective and subjective inequalities among both the most frustrated (Somali) and the most privileged (Kikuyu) groups in Kenya, this was not the case for larger groups without a history in power (2010 data; Langer & Mikami, 2013).…”
Section: Theorizing Support For Redistributionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it turns out, the limited amount of research conducted on subjective HIs also shows that perceptions of HIs may differ markedly from more objective assessments of these HIs (see, e.g., Kraus et al, 2017). Illustratively, Langer and Smedts (2013) find notable mismatches between objective and subjective HIs in 19 African countries. Hence, they conclude that "the assumption that objective and subjective HIs are largely the same…needs to be revisited and challenged" (p. 2).…”
Section: Demand For (Horizontal) Redistribution: Insights From Previo...mentioning
confidence: 99%